What is morphology? - Aronoff, Mark; Fudeman, Kirsten (Fundamentals of Linguistics, 2023)
"The term morphology is generally attributed to the German poet, novelist, playwright, and philosopher Johann Wolfgang von Goethe (1749-1832), who coined it early in the nineteenth century in a biological context. Its etymology is Greek. Morph- means 'shape, form', and morphology is the study of form or forms. In biology morphology refers to the study of the form and structure of organisms, and in geology it refers to the study of the configuration and evolution of land forms. In linguistics morphology refers to the mental system involved in word formation or to the branch of linguistics that deals with words, their internal structure, and how they are formed"--